NATIONAL HEROES IN THE INDONESIAN REVOLUTION AND THE MEANING FOR YOUNG GENERATION - Ida Bagus Brata; Ida Bagus Rai; Ida Bagus Seloka (International Journal of Social Science, 2021)
Awareness of Indonesian nationalism reached its peak after independence. The heroic values ​​inherited by historical actors must be imitated by the next generation of this nation. This paper explored the national heroes in the Indonesian revolution and their meaning for the younger generation. The method used in reviewing the problem is a literature study by studying various sources such as books, published scientific articles that are relevant to the research study. The results of the study showed that in the context of inheritance, a comprehensive understanding of the values ​​of heroism is needed so that the meaning and spirit of Indonesian nationalism continued to prioritize the ideals of the nation so that it could exist more in the midst of a highly competitive global era. Today's life is coloured by various competitions in line with the universal process marked by the loosening of national boundaries so that the challenges faced by a nation are increasingly complex. The younger generation of the nation's successors is required to appear in front of taking a role in global competition. However, in order not to lose direction and even identity, the figure of a hero in wartime who was so instrumental in politics and diplomacy, and in the post-independence period needs to be followed by the younger generation in fulfilling independence and continuing their ideals of struggle